Uji Efek Antidiabetes Ekstrak Daun Hibiscus surattensis L. Pada Mencit (Mus musculus) Jantan Dengan Mentode Toleransi Glukosa dan Induksi Aloksan - Revina Triani; Ramadhanil Ramadhanil; Yuliet Yuliet (Biocelebes, 2015)
Diabetes is a clinical syndrome characterized with an improvement of blood glucose or hyperglycemia which is caused by relative or absolute insulin deficiency, and can cause protein and fat metabolism disorder when it is untreated as soon as possible. The technology and science advance is not able to rule out traditional cure of anti-diabetic which is from local wisdom in society. The society of Sumari is one of the Indonesians whom utilizes plants as a herbal cure. A Hisbiscussurattensis L leaf or the local name “tamoenju” is utilized by the society of Sumari as an anti-diabetic herbal hereditary to lower the level of glucose. Therefore, it is necessary for scientific evidence regarding the effects of hypoglycemic on the plant in two methods; those are oral glucose tolerance test and alloxan induction. Hibiscus surattensis L extract was taken trough distillation process with 96% of ethanol as a solvent. Male mice (Mus musculus) were divided into five groups of treatment, namely negative control Na CMC, glibenclamide positive control, dosages 500 mg/Kg BB, 750 mg/Kg BB, and 1000 mg/Kg BB, where the acquired result of the research indicated that the Hibicus surattensis L leaf extract with 750 mg/Kg BB dosage has the most effective activities of hypoglycemic as an anti-diabetic. Keywords: Hibiscus surattensis L, anti-diabetic, Glucose Tolerance, Alloxan Induced.